AGROECOLOGICAL PROJECTS: CASE STUDY IN PUBLIC UNIVERSITIES - Augusto de Souza Aguiar, Bruno; Martins da Silva, Josemário; Simone Gonçalves Rosa Pacheco, Clécia (Journal of Interdisciplinary Debates, 2023)
The assessment of agroecological projects conducted by the Federal University of the São Francisco Valley (UNIVASF) and the State University of Bahia (UNEB) was incorporated into the curriculum activities of the Agroecology course, which is part of the Doctoral Program in Human Ecology and Environmental Management (PPGEcoH/UNEB). This study theoretically details two sustainability-focused projects: the “Sisteminha”, hosted by UNIVASF, and the “Caerdes”, implemented by the Center for Agroecology, Renewable Energies, and Sustainable Development of UNEB. The applied methodology is grounded in a bibliographic approach, combined with a case study, and is of a qualitative, exploratory, and documentary nature. Data collection was carried out through direct on-site observations and notes in field journals. The visits to SISTEMINHA and CAERDES provided a firsthand view of the research area and the introduction of various agricultural practices based on agroecological principles, pinpointing challenges and potential adaptations for the Semi-arid context. Both projects under review align with the organic agriculture concepts discussed in the classroom. However, to maximize their impact and relevance for family farmers, certain adjustments and enhancements need to be considered.